THEMES AND MORAL VALUES OF STORIES FROM THE SUB-CONTINENT PUBLISHED IN YOUTUBE - Bambang Yudi Cahyono (University of Muhammadiyah Purwokerto, 2013)
YouTube, a popular video site in the Internet, publishes children stories which can be used for the teaching of English. Many children stories published in YouTube are based on famous fairy tales like “Goldilock and the Tree Bears,” “The Three Little Pigs,” and “The Frog Prince.” Many other children stories, especially those from the Sub-continent, are based on the less famous tales. Examples of these stories include “The Four Friends,” “The Wise Son,” and “Whispering Palms.” Although these children stories are not well-known, with their clear English pronunciation and English subtitles they offer useful resources for the teaching of English. This paper presents the results of content analysis of a sample of 10 children stories from the latter category, that is children stories from the Sub-continent. The analysis was focussed on the themes and moral values. The results of analysis show that the children stories contain everyday life and animal life themes which are close to children life. The children stories also contain moral values which promote the importance of friendship, respect to other people, and love of natural environment. With examples of themes and moral values as such, the children stories from the Sub-continent are relevant with the mission in the development of character. Thus, when used in the English classroom, the video-based children stories from the Subcontinuent published in YouTube not only provide useful materials for the teaching of English, but they also contribute to the development of students’ good character.